Accuracy of working diagnosis by paramedics for patients presenting with dyspnoea. (10th July 2016) - Christie, Andrew; Costa‐Scorse, Brenda; Nicholls, Mike; Jones, Peter; Howie, Graham
Abstract: Objective: The present study aims to determine the agreement between paramedic and ED or hospital working diagnosis in dyspnoeic patients. Methods: Non‐consecutive written patient report forms were retrospectively audited for patients suffering from dyspnoea, who were transported to a tertiary hospital ED by ambulance paramedics. Accuracy of the paramedic working diagnosis was assessed by comparing agreement with either the primary or secondary ED diagnoses or hospital discharge diagnosis. Results: The study cohort was 293 patients. Exact agreement between paramedic versus ED or hospital diagnosis was 64%, 95% CI 58–69, k = 0.58, 95% CI 0.52–0.64. Only 226 (77%) had a 'clearly documented' paramedic diagnosis. Among these, agreement with either ED or hospital diagnosis was 79%, and there was a trend towards more agreement as paramedic level of practice increased (74%, 78% and 87% for Basic, Intermediate and ALS paramedics, respectively, P = 0.07). Conversely, ALS paramedics were less likely to document a working diagnosis (30/98, 31%) compared with Intermediate (22/102, 23%) and BLS paramedics (15/93, 16%), P = 0.008. Diagnostic agreement varied according to medical condition, from anaphylaxis (100%) and asthma (86%) to acute pulmonary oedema (46%). Conclusions: There was moderate agreement between paramedic and ED or hospital diagnosis. The number of cases with no clearly documented working diagnosis suggested that a singular working diagnosis may not always serve the complexity of presentation of some dyspnoea patients: more open descriptors such as 'mixed disease' or 'atypical features' should be encouraged.